2008
DOI: 10.1016/j.jaci.2007.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of GATA3 and IL13 gene polymorphisms associated with childhood rhinitis and atopy in a birth cohort

Abstract: Background-GATA3 activates transcription of the T H 2 cytokines, including IL13, an important step in the allergic inflammatory pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 31 publications
2
15
0
Order By: Relevance
“…Finally, we found a borderline association between IL13 rs1800925 and the risk to develop allergic rhinitis, confirming the data reported by Huebner et al (21) in a cohort of 923 children and by Black et al (22) in the longitudinal 1946 birth cohort study of the UK Medical Research Council's National Survey of Health and Development. 0, 1, and 2 represent the number of major, heterozygote and minor genotypes, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…Finally, we found a borderline association between IL13 rs1800925 and the risk to develop allergic rhinitis, confirming the data reported by Huebner et al (21) in a cohort of 923 children and by Black et al (22) in the longitudinal 1946 birth cohort study of the UK Medical Research Council's National Survey of Health and Development. 0, 1, and 2 represent the number of major, heterozygote and minor genotypes, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…14 IL-1312044G/A (rs20541) is a single nucleotide polymorphism (SNP) in the coding region of this gene; expression of this IL13 variant was associated with asthma, 15,16 atopy, 17 and increased total serum IgE levels in a birth cohort. Previous studies of IL13 polymorphisms and AR reported that SNPs in GATA3 (rs105820) and IL13 (rs1800925) interacted to affect the risk for AR 18 ; this same IL13 polymorphism was associated with the development of AR in our study of a Korean population. 19 We investigated whether the IL1312044G/A polymorphism interacts with environmental factors to affect the risk for AR.…”
supporting
confidence: 66%
“…Several studies have addressed a possible genetic interaction between SNPs of the IL13 and IL4R gene, yet with different asthma and allergic phenotypes and variable polymorphisms [22,23,24,25], or with other genes [26,27]. The odds ratio for asthma in the current study was greater with polymorphisms Arg130Gln and Glu375Ala than with the polymorphisms C–1111T and Ser478Pro, suggesting an additive effect.…”
Section: Discussionmentioning
confidence: 51%